The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fpls.2023.1212806
|View full text |Cite
|
Sign up to set email alerts
|

A SNARE-like protein from Solanum lycopersicum increases salt tolerance by modulating vesicular trafficking in tomato

Abstract: Intracellular vesicular trafficking ensures the exchange of lipids and proteins between endomembrane compartments. This is relevant under high salinity conditions, since both the removal of transporters and ion channels from the plasma membrane and the compartmentalization of toxic ions require the formation of vesicles, which can be maintained as multivesicular bodies or be fused to the central vacuole. SNARE proteins (Soluble N-ethylmaleimide-sensitive factor attachment receptor) participate in the vesicle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Significant progress has been made in understanding more sophisticated subcellular mechanisms of tolerance in tomato plants. Recent research has revealed that cellular damage repair systems and ion compartmentalization, based on vesicle trafficking, play a fundamental role in adaptation to saline conditions [6][7][8]. These emerging mechanisms provide a more comprehensive understanding of how plants respond and adapt to saline environments, opening new perspectives for genetic improvement strategies and agricultural practices that promote stress tolerance in tomato crops.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in understanding more sophisticated subcellular mechanisms of tolerance in tomato plants. Recent research has revealed that cellular damage repair systems and ion compartmentalization, based on vesicle trafficking, play a fundamental role in adaptation to saline conditions [6][7][8]. These emerging mechanisms provide a more comprehensive understanding of how plants respond and adapt to saline environments, opening new perspectives for genetic improvement strategies and agricultural practices that promote stress tolerance in tomato crops.…”
Section: Introductionmentioning
confidence: 99%